Examining Price Transparency in Grab Food Promotions through an Islamic Legal Perspectives - Putri, Winda Adhisa Triana; Fillah, Muhammad Machbub (Islamic Economic Law Study Program, Faculty of Sharia Sultan Aji Muhammad Idris Samarinda Islamic State University, 2024)
Grab is a company that provides various services, including food delivery services, also known as Grab Food. Chick Chick Fried Chicken Samarinda is one of the merchants registered with the Grab Food service and has successfully attracted public interest. Chick Chick Fried Chicken Samarinda applies different prices at each branch. However, this price difference only applies to the Grab Food service. Meanwhile, for offline purchases, there is no price difference between branches. So, this difference creates a price difference at each Chick Chick Fried Chicken Samarinda branch on the Grab Food application. So, this research aims to find out: 1) contract practices for Grab Food services at Chick Chick Fried Chicken Samarinda, 2) factors that cause price differences in Grab Food services at Chick Chick Fried Chicken Samarinda, and 3) how Islamic law views price differences at Grab Food service at Chick Chick Fried Chicken Samarinda. This type of research is normative-empirical research using a conceptual approach (conceptual approach) related to the concept of price in Islam. The research method used is qualitative, where the data analysis is descriptive-analytic. The results of this research explain that the contract practices between Grab Food and Chick Chick Fried Chicken Samarinda use the contracts of ijarah, samsarah, salam, istishna', wakalah, wakalah bil ujrah, qardh, and buying and selling. The contract transaction mechanism on the Grab Food service is included in the multi-contract mujtami'ah type. Factors influencing the price difference for Grab Food services at Chick Chick Fried Chicken Samarinda are administration fees (said) to PT. Grab Indonesia is 20% (twenty percent), and there is a margin discount from promotions held by Chick Chick Fried Chicken Samarinda and the implementation of cross subsidies for each branch. According to Islamic law, the price difference applied by Chick Chick Fried Chicken Samarinda to the Grab Food service is permissible, because it is done based on mutual consent and there is no coercion between the two.